AUTISM AND SOCIETY: NAVIGATING A SPECTRUM OF UNDERSTANDING - Gaur, Vandana; Bhatt, Anil; Gupta, Neeta; Parveez, Shaina (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article explores the interaction of ASD with the social contexts from historical perspectives, societal perceptions, and the growing levels of understanding of this neurodevelopmental disorder. The autism spectrum, with its variations in skills and challenges, is explored in respect of education, employment, family dynamics, self-advocacy, and cultural expressions. While significant progress has been made, individuals diagnosed with autism still struggle socially through stigma and misunderstanding. The article identifies the key factors that help enable a society that nurtures the growth and development of autistic individuals: inclusion, fighting stereotypes, and becoming aware of neurodiversity. This article develops an integrated approach drawing from academic scholarship, policy frameworks, and cultural portrayals and hence offers a panoramic view of autism in society speaking toward a future marked by understanding, acceptance, and meaningful inclusion.